ANALISA INDIKATOR KESELAMATAN PELAYARAN PADA KAPAL NIAGA - Andi Hendrawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2019)
Shipping safety is very important and occupies a central position in all aspects of the shipping world. Aspects inherent in shipping safety include the characteristics of attitudes, values, and activities regarding the importance of fulfilling safety and security requirements concerning transportation in waters Ship and shipping safety indicators are two sides that are not separated, the ship must have safety equipment including lifeboats, life jackets, fire extinguishers, documents and certificates, the ship's screen-worthy condition. The health of the crew, all must be properly prepared and ascertained the existence and circumstances so that the cruise will be safe and secure.